LA LEGISLACIÓN DE LA “BONIFICACIÓN” EN ITALIA Y LOS CONSORCIOS DE “BONIFICACIÓN” DE AGUAS - Galvani, Adriana (M+A. Revista Electrónica de Medioambiente, 2008)
Land reclamation is an ancient practice in Italy, going back to Etruscan, Roman, Renaissance ages. One of the first State legislation occurred at the end of the XIX century, after the Italian State unity. The most important and decisive law was the Royal Decree of 1933, proposing the "integral reclamation", suggesting the necessity of an integrated amelioration of physical, social, demographic, hygienic, cultural aspect of poor agrarian areas. The law presented not only the activity of recuperation, but also of general development in a poor State where agriculture was the basic activity. In this way we assist at the passage from land repossession to territorial organization. This project culminated in 1950 with the "Agrarian Reform" which determined a redistribution of big properties in favor of landless laborer. 11 7M+A. Revista Electrónic@ de Medioambiente 2007,4: 11-17 La Legislación de la bonificación en Italia y los Consorcios de bonificación de Aguas GALVANI, A. This has been the last law favoring reclamation and the related works ended in the seventies, because nowadays marshlands are protected, especially, the vast amount of marshes along the Po Delta. The activity of water regulation in Italy is nowadays deputed to the "Consorzi di Bonifica or "Reclamation Consortia".